(a) x represents the cost of Peyton's item.
Since, Peyton bought 3 items, total cost paid by Peyton = 3x
It is given that Joe's item is $2.25 less than Peyton's.
Therefore, cost of Joe's item = x - 2.25.
Since, Joe bought 4 items, total cost paid by Joe = 4(x - 2.25).
Since both paid the same amount of money,
3x = 4(x - 2.25)
(b) 3x = 4(x - 2.25)
3x = 4x - 9
3x - 4x = -9
-x = -9
x = 9
(c) Check:
Amount spent by Peyton = 3x = 3(9) = $27.
Amount spent by Joe = 4(x - 2.25) = 4(9 - 2.25) = 4(6.75) = $27.
According to the problem, since both are same, our solution x = 9 is correct.
(d) The solution x = 9 is the cost of each item bought by Peyton and x - 2.25 = 9 - 2.25 = 6.75 is the cost of each item bought by Joe.